Human Resource Management and Digitalization in a South African Public Enterprise - Arvid Muzanenhamo; Edward Rankhumise (CV. Literasi Indonesia, 2023)
Although digitalization has been experienced in many business operations, we are still lacking complete knowledge of the impacts of the application of these technological operations in Human Resource Management (HRM) at both an individual level and organizational level. This paper, therefore, seeks to clarify the importance of digitalization to organizations and the challenges facing HRM due to the lack of digitalization. This paper is a study carried out in a South African public enterprise to identify the organizational effects of lack of digitalization in the Human Resource Management department. Qualitative research was applied and interviews were used to gather data from Human Resource professionals and section managers in a public corporation. Twenty-four individuals were purposively chosen for data collection. The research discovered effects such as lack of digital training, the occurrence of errors, service delays, and the possibility of employee burnout due to manual systems used to serve a large organization. The discussion provided in this study would strengthen the body of knowledge on the importance of digitalization in public enterprises, especially public organizations that have a role to protect national security.